Device for continuous assessment of uniaxial stress of existing masonry structures: Laboratory validation. Issue 5 (4th March 2019) - Boffill, Yosbel; Blanco, Haydee; Lombillo, Ignacio; Villegas, Luis
Summary: Knowledge of the mechanical characteristics of the materials and the behaviour of the structure play an important role in the process of intervention in ancient buildings. Moreover, the heterogeneity of these structures and/or the necessity to know how effective a reinforcement will be, among other aspects, make it necessary to propose new devices and/or techniques that enable the characterisation and evaluation of the associated masonry structures. This paper presents a slightly destructive technique for continuous monitoring of stress variations undergone by existing masonry structures. It is based on the estimation of the existing stress state, and its continuous monitoring over time. The development methodology and the validation of results obtained by the stress device in laboratory are discussed. To do so, among other factors, the effect of temperature variations on the sensor records are analysed, and the relationship between the stress variations and the displacements recorded in the monitored area are evaluated. After 10 months of continuous monitoring, it could be concluded that there was a good relationship between the stress variations applied in the masonry wall and the stresses measured by the device. Besides, a notable influence of the thermal variations on the sensor registers was found. A thermal correlation coefficient was proposed, which minimised the thermal incidence on the stresses registered. Moreover, a suitable relationship was also confirmed between the manual and continuous deformation measurements. The results show the capability of the proposed device to evaluate the continuous stress monitoring of existing masonry structures during intervention processes.